2022
DOI: 10.1038/s41598-022-11891-5
|View full text |Cite
|
Sign up to set email alerts
|

Trophic and immunomodulatory effects of adipose tissue derived stem cells in a preclinical murine model of endometriosis

Abstract: Endometriosis, which exhibits enigmatic pathological features such as stromal fibrosis and proliferation of ectopic epithelial cells, is known as a refractory disease. Mesenchymal stem cells modulate the fibrosis in stromal tissues through their trophic and immunomodulatory properties. To investigate the potential of stem cells in treating endometriosis, we examined the secondary morphology and molecular alterations in endometriosis-like lesions after the administration of adipose tissue-derived stem cells (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The transfer of MSCs derived from normal adipose tissue leads to decreases in the size of ectopic endometrial lesions in rats with endometriosis due to the downregulation of proinflammatory cytokines, including IFN and TNFα, in peritoneal macrophages and ectopic endometrial lesions that are required for endometriosis progression [ 96 ]. In the murine model of endometriosis, intravenous administrated adipose tissue-derived MSC (Ad-MSC) directly migrates to endometriosis lesions and inhibits the growth of endometriosis lesions, by suppressing the expressions of proinflammatory cytokines, including monocyte chemotactic protein-1 ( MCP1 ), interleukin-6 ( IL6 ), and leukemia inhibitory factor ( LIF ) and pro-fibrotic cytokine such as tumor growth factor-β1 ( IGFB1 ) [ 97 ]. However, the efficacy of MSC therapy for endometriosis is still controversial.…”
Section: Dysregulation Of Interferon Signaling In Endometriosismentioning
confidence: 99%
“…The transfer of MSCs derived from normal adipose tissue leads to decreases in the size of ectopic endometrial lesions in rats with endometriosis due to the downregulation of proinflammatory cytokines, including IFN and TNFα, in peritoneal macrophages and ectopic endometrial lesions that are required for endometriosis progression [ 96 ]. In the murine model of endometriosis, intravenous administrated adipose tissue-derived MSC (Ad-MSC) directly migrates to endometriosis lesions and inhibits the growth of endometriosis lesions, by suppressing the expressions of proinflammatory cytokines, including monocyte chemotactic protein-1 ( MCP1 ), interleukin-6 ( IL6 ), and leukemia inhibitory factor ( LIF ) and pro-fibrotic cytokine such as tumor growth factor-β1 ( IGFB1 ) [ 97 ]. However, the efficacy of MSC therapy for endometriosis is still controversial.…”
Section: Dysregulation Of Interferon Signaling In Endometriosismentioning
confidence: 99%
“…ASC isolation was conducted in accordance with a previously documented protocol [ 36 ]. In brief, subcutaneous adipose tissue specimens were obtained from ICR mice to procure adipose-derived regenerative cells (ADRCs).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometric analyses of ASCs were performed according to a previously reported protocol [ 36 ]. In brief, ASCs were suspended in a staining buffer (R&D Systems, Minneapolis, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Umbilical cord (UC)‐derived MSCs (UC‐MSCs) inhibit endometriotic cell proliferation in vitro 5,6 . In rodent models, adipose tissue‐derived stem cells inhibited the growth of endometriosis‐like lesions 7,8 . In contrast, Abomaray et al demonstrated that MSCs derived from ectopic and eutopic endometrial tissues are pluripotent and support the growth of endometriotic lesions through immunosuppressive effects 9 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In rodent models, adipose tissue-derived stem cells inhibited the growth of endometriosis-like lesions. 7,8 In contrast, Abomaray et al demonstrated that MSCs derived from ectopic and eutopic endometrial tissues are pluripotent and support the growth of endometriotic lesions through immunosuppressive effects. 9 The same authors also concluded that the use of adipose tissue-derived MSCs should not be considered a potential therapy for endometriosis.…”
mentioning
confidence: 99%